Inhibition of DNA Topoisomerase Type IIα (TOP2A) by Mitoxantrone and Its Halogenated Derivatives: A Combined Density Functional and Molecular Docking Study. (15th February 2016) - Abu Saleh, Md.; Solayman, Md.; Hoque, Mohammad Mazharol; Khan, Mohammad A. K.; Sarwar, Mohammed G.; Halim, Mohammad A.
Abstract : In this study, mitoxantrone and its halogenated derivatives have been designed by density functional theory (DFT) to explore their structural and thermodynamical properties. The performance of these drugs was also evaluated to inhibit DNA topoisomerase type II α (TOP2A) by molecular docking calculation. Noncovalent interactions play significant role in improving the performance of halogenated drugs. The combined quantum and molecular mechanics calculations revealed that CF3 containing drug shows better preference in inhibiting the TOP2A compared to other modified drugs.